Rethinking the Concept of Learning Disability. - Penney, Catherine G. (Canadian Psychology / Psychologie Canadienne, 2018)
Learning disabilities are assumed to result from a neurological disorder that makes it very difficult for children to perform well in school. The unstated assumption is that there is a discontinuity in the distribution in aptitude for academic studies such that these children can be objectively categorised as having a learning disability or not. This assumption is based on an analogy with medical diseases or disorders in which certain tests can indicate whether or not a disease is present. However, this analogy is not appropriate and results in a number of practical problems. An alternate view is presented according to which the efficiency of mental processes required for learning to read or do mathematics varies on a continuum. If there is a continuum, attempts to develop objective criteria for diagnosing learning disabilities will necessarily be arbitrary, and will result in unfairness in provision of special resources. Rather than focusing on diagnosing learning disabilities to determine which children get special help, the suggested goal is to develop curricula in academic subjects that allow for individualized academic programs. In this way, all children would progress at their own pace always being mildly challenged and mastering the material before progressing to new topics.